BayesTwin: An R Package for Bayesian Inference of Item-Level Twin Data - Schwabe, Inga (Journal of open research software, 2017)
BayesTwin is an open-source R package that serves as a pipeline to the MCMC program JAGS to perform Bayesian inference on genetically-informative hierarchical twin data. Simultaneously to the biometric model, an item response theory (IRT) measurement model is estimated, allowing analysis of the raw phenotypic (item-level) data. The integration of such a measurement model is important since earlier research has shown that an analysis based on an aggregated measure (e.g., a sum-score based analysis) can lead to an underestimation of heritability and the spurious finding of genotype-environment interactions. The package includes all common biometric and IRT models as well as functions that help plot relevant information or determine whether the analysis was performed well. Keywords: Heritability, Bayesian inference, Twin data, Genetics, Item response theory, Measurement error, Genotype-environment interaction, R, Software package